Dix and Crump on contracts of employment : sixth edition supplement - Crump, D. W. (London : Butterworths, 1983)
A supplement of the sixth edition of Dorothy Knight Waddy's book 'Dix and Crump on contracts of employment'. It takes into account the unabated spate of legislation and case law affecting individual employment relationships since the publication of the sixth edition.
oif 29/01/2019
Loans
Keywords: Labour contract; Labour laws and legislation